Hiking Washington's History - Bentley, Judith M; Romano, Craig (Book collections on Project MUSE., 2021)
"For thousands of years people have traveled across Washington's spectacular terrain, establishing footpaths and roads to reach hunting grounds and coal mines high in the mountains, fishing sites and trade emporiums on the rivers, forests of old growth, and homesteads and towns on prairies. These traditional routes have been preserved in national parks, restored by cities and towns, salvaged from old railroad tracks, and opened to hikers by Indigenous communities. In this new, full-color edition of the first-ever hiking guide to650 the state's historic trails, historian and hiker Judy Bentley teams up with veteran guidebook author Craig Romano to lead adventurers of all abilities along trails on the coast, over mountains, through national forests, across plateaus, and on the banks of the Columbia River. Features include: 44 hikes, including 12 new additions Full-color trail maps A trails timeline that connects hikes to key events Updated trail descriptions Accounts from diaries, journals, and archives Historical overviews of 8 regions of the state Contemporary and historical photographs Bentley and Romano offer an essential boots-on-the ground history of some of the state's most fascinating places"--